Strategies towards endo-type B polycyclic polyprenylated acylphloroglucinols: total synthesis of regio-hyperibone L and (+)-epi-clusianone. Issue 11 (31st March 2021) - Wang, Liping; Wang, Xueying; Zhang, Guocai; Fu, Wenwei; Zhang, Hong; Zhou, Hua; Xu, Hongxi; Zheng, Changwu
Abstract : The first and general method for the total synthesis of regio -hyperibone L and (+)- epi -clusianone via domino Dieckmann cyclization was developed. Abstract : A concise and stereoselective method toward the divergent synthesis of polycyclic polyprenylated acylphloroglucinols and the analogues in both racemic and asymmetric fashions was developed. With the bioinspired Me2 AlSEt-promoted domino Dieckmann cyclization as the key strategy, the total synthesis of regio -hyperibone L and the first asymmetric total synthesis of natural epi -clusianone were achieved, which determined the absolute configuration of epi -clusianone and demonstrated the broad synthetic applicability of the domino method. Furthermore, by a stereoselective alkylation/reductive deprotection/cyclization strategy, the key enantioenriched 5-substituted lactones for accessing epi -clusianone are prepared efficiently, which provides a general asymmetric approach towards the synthesis of endo -type B PPAPs.